Sistem Informasi Perpustakaan SMK N 3 Kendal Berbasis QR Code - B. Suhartono; Fella Fella (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
The SMK N 3 Kendal Library is a vital resource supporting teaching and learning activities at the school. However, the manual process of registering and identifying library members often presents various challenges, such as data entry errors, service delays, and difficulties in membership verification. Based on these challenges, a QR Code-based member and library book registration system was designed and developed to improve the efficiency and accuracy of membership data management. This system was built using the Waterfall system development method, with stages including needs analysis, system design, implementation, testing, and maintenance. QR Code technology serves as a unique identifier for each member, stored in the database and can be scanned using a digital device to expedite the identification process. System testing results indicate that implementing QR Codes in the member registration system can accelerate the library's book borrowing process at the school, including registration, data retrieval, and member verification, by up to 80% compared to manual methods. Therefore, this system can help the library improve service effectiveness, minimize data input errors, and support more modern and integrated library administration.